A controlled survey of sacroiliitis in Behçet's disease. Issue 6 (December 1981) - Yazici, H.; Tuzlaci, M.; Yurdakul, S.
Abstract : Among 37 patients with Behçet's disease in Turkey the radiographic presence of sacroiliitis was no more frequent than in 28 age and sex matched controls.